One new variety of the genus Thespesia Soland. ex Corr. (Malvaceae Juss.) for the flora of Vietnam - Xuyen, Do Thi (Academia Journal of Biology, 2014)
One new variety of the genus Thespesia Soland. ex Corr. (Malvaceae Juss.) for the flora of Vietnam